Face mask management system for the control of supplies of medical personnel in the private sector - Meneses Claudio, Brian Andreé (2023)
In late December 2019, COVID-19 changed people's lives by forcing people to maintain social distancing and wear a face mask on a mandatory basis, because the virus caused by SARS-COV-2 is immensely contagious and can be easily transmitted between people who have direct contact. In the month of May, the virus infected more than 153 million people saturating the health system worldwide, therefore, it was established as a preventive measure to maintain social distancing in public places and use the face mask in a mandatory way to help control COVID-19, since through these measures the probability of contagion is greatly reduced since it protects the nose and the person's mouth. In view of this problem, this article made the approach of a system of administration of face masks for the control of supplies of medical personnel in the private sector, in such a way that the system analyzes several people who enter the place and shows if they use the mask correctly through a monitor, requiring to respect this important biosecurity measure, in addition to being able to make a report detailing the supplies of face masks to send to the administrator in charge. Through the development of the system, it is determined that the system works in the best way and presents a percentage of efficiency of 97.12% in detecting the face masks of medical personnel.